Prawda w mediach - Zanussi, Krzysztof (Annales. Etyka w Życiu Gospodarczym, 2008)
It used to be that if some message came from an oral source, its weight depended on reliability of the one who had transmitted it and on the one who had heard it. If, on the other hand, something was printed it intrinsically became credible. Democratization of access to print and similar democratization of media, apart from its undoubtedly positive side, brings also a negative novum – it encourages everyone to speak freely. It is impossible to talk about truth in media, or truth in any other sense, and not relate to the fashionable nowadays in the humanities the vanquisher of Marxism – called postmodernism. This very movement in its popular form sows the seeds of fear of all who proclaim the existence of objective truth or, what is worse, absolute truth. They caution that the supporters of this truth will introduce it by force, so we are in danger of facing totalitarianism, fundamentalism and dark dictatorship. It is uncertainty that drives people to violence. Those who have something to hold on to are more unaffected by despair. The fanatics are often recruited from those who are adrift. Less often from those with a questing mind. But in order to seek one needs to believe that truth exists. Even if it were always incomplete and imperfect in the form in which we are able to assimilate it. To the charges that every certainty leads to violence, I reply that most frequently it is the opposite. It is fear and feeling adrift that drive people to the false certainty. Whoever believes that truth exists will easier accept that he will never grasp it. In the very important debate that was conducted some years ago, the fear of fundamentalism was juxtaposed with the fear of nihilism. I see the latter as a greater threat.